2019
DOI: 10.1186/s13014-019-1317-x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hypofractionated radiotherapy plus chemotherapy for inoperable locally advanced non-small-cell lung cancer: final results of a prospective phase-II trial with a long-term follow-up

Abstract: Background Concurrent chemotherapy and radiation using conventional fractionation is the standard treatment for inoperable, locally advanced non-small-cell lung cancer (NSCLC). We tested accelerated hypofractionated radiotherapy (AHR) and chemotherapy for the treatment of locally advanced NSCLC. Methods Eligible patients with locally advanced NSCLC were treated with induction chemotherapy (cisplatin and docetaxel), followed by AHR using tomotherapy and consolidation che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Some reports contain only toxicity by group (e.g., only > grade 2), some do not distinguish between early and late toxicity, while most consider a short follow-up for toxicity occurrence and do not take into account specific toxicity of late-responding tissues (stricture, fistula, hemorrhage) (62). To illustrate this, the reported outcomes are summarized in Table 1, with a focus on toxicity in the published prospective studies on moderate hypofractionation without the use of concurrent CHT (63)(64)(65)(66)(67)(68)(69)(70)(71)(72).…”
Section: Hypofractionation: Moderate Hypofractionation With or Without Chtmentioning
confidence: 99%
“…Some reports contain only toxicity by group (e.g., only > grade 2), some do not distinguish between early and late toxicity, while most consider a short follow-up for toxicity occurrence and do not take into account specific toxicity of late-responding tissues (stricture, fistula, hemorrhage) (62). To illustrate this, the reported outcomes are summarized in Table 1, with a focus on toxicity in the published prospective studies on moderate hypofractionation without the use of concurrent CHT (63)(64)(65)(66)(67)(68)(69)(70)(71)(72).…”
Section: Hypofractionation: Moderate Hypofractionation With or Without Chtmentioning
confidence: 99%
“…He was enrolled in a prospective phase II clinical trial of CRT using AHRT in helical TomoTherapy (TomoTherapy Inc., Madison, WI, United States) for patients with LA-NSCLC (EudractCT registration 2008-006525-14)[ 10 ].…”
Section: Treatmentmentioning
confidence: 99%
“…To plan RT, the patient underwent a multiphasic chest contrast-enhanced free-breathing CT scan to obtain the best definition of tumor and infiltration of organs at risk (OaR). Information on contouring and RT planning are reported in the protocol[ 10 ] (Figure 2 ). Radiological evaluation, PET-CT and total body contrast-enhanced CT scan performed at the end of the protocol showed a reduction in the primary tumor mass, left parahilar mass (standardized uptake value, 4 vs 8.93 pre-RT), no evidence of radiological mediastinal nodes, and the appearance of pulmonary thickening in the lower left lobe.…”
Section: Treatmentmentioning
confidence: 99%
“…CCRT with a double-drug regimen in lung cancer and cervical cancer is approved and widely used in clinical practice 16 , 17 . Radiotherapy combined with docetaxel is feasible and is widely used in non-small-cell lung cancer (NSCLC) and cervical cancer 18 , 19 . Recently, a study demonstrated that CCRT combined with a small weekly dose of docetaxel is an effective and tolerable treatment for locoregionally advanced NPC 20 .…”
Section: Introductionmentioning
confidence: 99%